GAYA KEPEMIMPINAN OTORITER (OTOKRATIS) DALAM MANAJEMEN PENDIDIKAN - Wahyuni, Sri; Sukatin, Sukatin; Fadilah, Inda Nur; Astri, Winda (Department of Islamic Education Management, 2022)
Abstract: Authoritarian Leadership Style (Autocitas) in Education ManagementThis paper was made to find out the impact of Authoritarian Leadership Style (Otokritas) in Education Management with Literature research methods by gathering various sources of writing sources to get specific conclusions, from this study it can be known that the model of Authoritarian Leadership (Otokritas) has a positive and negative impact. Among them can improve the work discipline of Educators and Education Personnel but many adverse effects of this Authoritarian leadership Style are that educators and educators tend to be passive and uncreative, and the lack of family in schools because educators and educators tend to feel afraid by the principal. Abstrak: Gaya Kepemimpinan Otoriter (Otokritas) dalam Manajemen PendidikanTulisan ini dibuat untuk mengetahui dampak Gaya Kepemimpinan Otoriter (Otokritas) dalam Manajemen Pendidikan dengan metode penelitian Kepustakaan dengan mengumpulkan berbagai sumber sumber tulisan untuk mendapatkan kesimpulan secara khusus, dari penelitian ini dapat diketahui bahwa model Kepemimpinan Otoriter (Otokritas) memiliki dampak positif dan negative. Diantaranya dapat meningkatkan disiplin kerja para Pendidik dan Tenaga Kependidikan tetapi banyak dampak buruk dari Gaya kepemimpinan Otoriter ini yaitu membuat Pendidik dan Tenaga Pendidik cenderung bersifat pasif dan tidak kreatif, dan kurangnya Kekeluargaan didalam Sekolah karena Pendidik dan Tenaga Pendidik cenderung merasa takut oleh Kepala Sekolah